Faktor-Faktor yang Mempengaruhi Minat Belajar Siswa Mata Pelajaran Al-Qur’an Hadits - Nopita Sari Nopi (Pusat Studi Pesantren dan Pemberdayaan Masyarakat, LPPM, Universitas Brawijaya, 2022)
This study discusses the results of the factors that influence students' learning interest in the Qur'an Hadits subject. To accomplish this objective, we identified 30 students on X grade and 29 students on XI grade. This study reports on a descriptive analysis method. I use confirmatory factor analysis using computer software tools in the form of visual PLS to analyse the validity. Results indicate that the factors that influence students' learning interest in the Qur'anic subject consisted of three factors, namely self factor with a total average 71.91% in the medium category, the madrasa environment factor obtained total average 83.35% in the high category, and the family and community environment factor are obtained with a total average 67.07% in the medium category. Recommendation to influence students’ interest in Qur'an Hadits subject in senior high school are provided.